Social Problems In The Novel Bumi Manusia By Pramoedya Ananta Toer (A Sociological Review Of Literature) - Ridwan Tawaqal; Nurhadi; Berliana Wahyu Ningtyas (International Journal of Education, Vocational and Social Science, 2025)
The purpose of this study is to examine the social problems in Pramoedya Ananta Toer's novel "This Earth of Mankind" (Bumi Manusia) and to uncover the social issues contained within the novel. The purpose of this study is to increase readers' knowledge of literary studies, particularly the sociology of literature, and to enhance readers' understanding of the social problems contained in Pramoedya Ananta Toer's novel "This Earth of Mankind." The method used in this study is descriptive qualitative. This type of research is library research. Based on the findings of this study, there are seven social problems contained in Pramoedya Ananta Toer's novel "This Earth of Mankind" (Bumi Manusia): poverty, crime, family disorganization, youth issues in modern society, war, violations of norms, and bureaucracy. Each of these social problems is cited. After conducting this research, we can see how difficult it was to live as an indigenous person during that era.